The effects of sex-biased fisheries on crustacean sex ratios and reproductive output. Issue 3 (3rd July 2019) - Ogburn, Matthew Bryan
ABSTRACT: Crustacean fisheries often preferentially or exclusively harvest males, resulting in selection that alters sex ratios in fished populations. Sex-biased fisheries may occur when males are larger and fisheries are size-selective, or when regulations limit or prohibit harvest of females to protect sufficient spawning stock to maintain the population. This review explores the evidence for fishery-induced alterations in sex ratios in crustacean fisheries and the resulting effects on reproductive output at the level of the individual and population. Crustacean fisheries exhibit substantial spatial and temporal variation in exploitation, which could lead to hotspots of altered sex ratios. Experimental manipulations simulating the effects of selective harvest indicate that altered sex ratios can lead to sperm limitation and reduction in the reproductive output of individual females. The effects of altered sex ratios on reproduction at the population scale remain poorly understood. Future directions for improving our understanding of the effects of altered sex ratios on reproductive output include focused studies on sperm limitation at high fishery exploitation rates, model simulations of population scale reproductive output that account for individual variation in sperm quantity, and detailed studies of sperm storage and use during fertilization.